2015
DOI: 10.1111/jpy.12304
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the dinoflagellate cyst Spiniferites pachydermus and Gonyaulax ellegaardiae sp. nov. from Izmir Bay, Turkey, and molecular characterization

Abstract: Here, we established the cyst-motile stage relation-ship for Spiniferites pachydermus through incubation of cysts with a characteristically microreticulate/perforate surface isolated from Izmir Bay in the eastern Aegean Sea of the eastern Mediterranean. The morphology of the motile stage was similar to Gonyaulax spinifera but had a different size, overhang, displacement and reticulations. Based on the distinct morphology of the cyst and morphological differences in motile cells, we assigned S. pachydermus from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 48 publications
(78 reference statements)
3
35
1
1
Order By: Relevance
“…The results of the present study clearly showed that the new dinoflagellate species described herein belongs to the genus Gonyaulax, but its morphological and molecular characteristics were different from those of any of the other 76 known species in this genus. The overall features of Gonyaulax whaseongensis match those of the spinifera group (Kofoid 1911), but the morphological characteristics of the motile cells are clearly different from those of the four previously described species belonging to the spinifera group (G. spinifera, G. digitale, G. diegensis, and G. areolata, Kofoid 1911, Kofoid andMichener 1911), as well as those of five other Gonyaulax species, G. membranacea, G. ellegaardiae, G. monospina, G. rotundata, and G. cochlea (Meunier 1919, Schiller 1937, Rampi 1951, Dodge 1988, 1989, Lewis et al 1999, Ellegaard et al 2003, Mertens et al 2015. The morphological characteristics of G. whaseongensis that distinguish it from these other species are: (i) narrow cingulum width (ca.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…The results of the present study clearly showed that the new dinoflagellate species described herein belongs to the genus Gonyaulax, but its morphological and molecular characteristics were different from those of any of the other 76 known species in this genus. The overall features of Gonyaulax whaseongensis match those of the spinifera group (Kofoid 1911), but the morphological characteristics of the motile cells are clearly different from those of the four previously described species belonging to the spinifera group (G. spinifera, G. digitale, G. diegensis, and G. areolata, Kofoid 1911, Kofoid andMichener 1911), as well as those of five other Gonyaulax species, G. membranacea, G. ellegaardiae, G. monospina, G. rotundata, and G. cochlea (Meunier 1919, Schiller 1937, Rampi 1951, Dodge 1988, 1989, Lewis et al 1999, Ellegaard et al 2003, Mertens et al 2015. The morphological characteristics of G. whaseongensis that distinguish it from these other species are: (i) narrow cingulum width (ca.…”
contrasting
confidence: 55%
“…, Mertens et al. ). The morphological characteristics of G. whaseongensis that distinguish it from these other species are: (i) narrow cingulum width (ca.…”
mentioning
confidence: 99%
“…In some recent cases, a new name was given to a living stage of an equivalent fossil-defined species. An example of this is the new name Gonyaulax ellegaardiae that was given to the motile stage and living cyst of the previously described cyst-defined fossil-species Spiniferites pachydermus (Mertens et al 2015). Here the species was defined on morphological characters of both motile and cyst stages, supported by DNA-sequence based phylogeny.…”
Section: Newer Cyst-motile Stage Linksmentioning
confidence: 99%
“…Here the species was defined on morphological characters of both motile and cyst stages, supported by DNA-sequence based phylogeny. The new species was proposed to correspond to the fossil cyst-defined species Spiniferites pachydermus (Mertens et al 2015), following the practice of dual nomenclature. The name Gonyaulax ellegaardiae might, prima facie, appear to have been superfluous when proposed because Mertens et al (2015) accepted its cyst as being equivalent to the existing fossil-defined species Spiniferites pachydermus.…”
Section: Newer Cyst-motile Stage Linksmentioning
confidence: 99%
See 1 more Smart Citation